2020
DOI: 10.1200/jco.2020.38.15_suppl.e16750
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism-based GP-2250 in combination with gemcitabine as a novel approach to pancreatic cancer: A mouse xenograft study.

Abstract: e16750 Background: GP-2250, a novel oxathiazine derivative, displayed apoptotic cytotoxicity against various tumor cell lines but not normal cells. It was therefore tested whether its antineoplastic potential - alone or in combination – could be leveraged specifically against pancreatic cancer. Methods: GP-2250 is a cancer metabolism-based therapeutic. It depleted metabolic energy through inhibition of the enzyme GAPDH (glyceraldehyde-3-phosphate dehydrogenase) which is rate limiting for aerobic glycolysis. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The clinical course of our PDX model Bo99 indicates a necessary second-line therapy with moderate side effects. The first experiments in pancreatic adenocarcinoma suggest a synergistic effect of the novel agents GP-2250 and Gemcitabine [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical course of our PDX model Bo99 indicates a necessary second-line therapy with moderate side effects. The first experiments in pancreatic adenocarcinoma suggest a synergistic effect of the novel agents GP-2250 and Gemcitabine [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has a six-ring structure with oxygen, sulfurdioxide and nitrogen atoms on the positions 1, 4 and 5, respectively. The exact mechanism of action is yet to be fully explored; the findings of our research group suggest the induction of cell death via the increased release of reactive oxygen species as well as mitochondrial dysfunction [ 20 , 21 , 22 ]. In vivo, GP-2250 shows the reduction of tumor growth in the xenografts of established pancreatic cancer cell lines, as well as in patient-derived xenograft (PDX) models of pancreatic adenocarcinoma, accompanied by rarely occurring side effects [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that GP-2250 has a synergistic antineoplastic effect when administered in combination with anticancer agents in patient-derived xenograft models [2,3]. GP-2250 shows promise as an effective adjuvant to conventional chemotherapeutics in human cancers and is currently being evaluated in a phase 1 dose-escalation study in patients with advanced pancreatic cancer (NCT03854110).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data from an in-vitro cell line assessment and a patient-derived xenograft model showed that GP-2250, when used in combination with other anticancer drugs, synergistically stabilized or regressed tumor growth [ 2 , 3 ]. The synergistic effect of GP-2250 with multiple anticancer agents provides strong proof of concept for GP-2250 as a promising new chemotherapeutic.…”
Section: Introductionmentioning
confidence: 99%
“…In nude mice, GP-2250 was safe, resulting in acute (2000 mg/kg BW) or chronic (1000 mg/kg BW) toxicity only at extremely high concentrations (Buchholz et al 2017 ). The same research group published further data on anti-neoplastic effects of GP-2250 on different malignancies (Braumann et al 2020 ; Baron et al 2022 ; Buchholz et al 2022 ). In a clinical phase I/II trial on patients with advanced pancreatic carcinoma, GP-2250 is currently investigated in combination with gemcitabine (clinicaltrials.gov: NCT03854110) (Geistlich Pharma 2020 ).…”
Section: Introductionmentioning
confidence: 98%